PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI DAN KUALITAS PELAYANAN PADA SISTEM ENTERPRISE RESOURCE PLANNING TERHADAP KEPUASAN PENGGUNA (Universitas Muhammadiyah Palembang, 2023)
Purpose– This study aims to determine the effect of system quality, information quality and service quality on the Enterprise Resource Planning (ERP) system on user satisfaction at PT. Orindo Alam Ayu Medan branch. Design/methodology– This research uses quantitative research methods. The population in this study are Oriflame members in Medan City. The sampling technique used was purposive sampling with a total sample of 100 respondents. Data collection techniques using a questionnaire with a Likert scale. Then the primary data obtained was processed through SPSS software version 29. Findings - The results showed that the quality of the system has no effect on user satisfaction. Information quality has a significant effect on user satisfaction and service quality has a significant effect on user satisfaction. Then simultaneously system quality, information quality, and service quality have a significant effect on user satisfaction of the Enterprise Resource Planning (ERP) system at PT. Orindo Alam Ayu Medan Branch.